Examination of the Current Deficit Asymmetric Behavior With the Markov Change Model: Turkey Example - Özek, Yavuz (My University, 2020)
The current account balance is one of the important indicators providing information about theeconomic performance of a country. An unbalanced current account is undesirable for economies. There aremany studies in the literature about The current account deficit (CAD) which is one of the most importantissue for specially Turkey and developing countries such as Turkey. Turkey has been struggling currentdeficit for many years. This study focused on determining the CAD using regime change model in order todemonstrate the asymmetric behavior of the CAD based on data from 1987:Q1 to 2012:Q4 in Turkey. In thiscontext, the data set was obtained from the database of the Turkish Statistical Institute and was free fromseasonality according to the Serial Tramo-Seats method. Markov regime change model developed byHamilton (1989) and Krolzig (1997,1998) to analyze augmented (Extended) Dickey-Fuller (1979, 1981ADF) unit root test and conjuncture waves as analysis method in the study has been implemented. Accordingto the findings obtained from empirical tests, the current account deficit in Turkey showed a contractionregime in the years of 1994, 2001 and 2008-2009 when economic crisis periods are experienced. In theseyears, when the contraction regime was observed, the current account deficit is decreasing due to theslowdown in economic growth and the import-dependent construction of exports. In studies conducted inother years, Turkey has shown an expansion regime. The increase in economic activities during theexpansion periods of the current account balance causes a high current account deficit.
Keywords: Siyasi Bilimler; İktisat; İşletme Finans